Peranan Pasar Modal Syariah di Era Informasi Keuangan Syariah Indonesia - Yusuf, Yusuf; Wulandari, Siti Pamrih Anjas (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
The existence of Islamic financial institutions in marketing the product in the information era influences society's enthusiasm to get the investment choice alternative. Economic impact pandemic virus Covid 19 gives the opportunity of product Islamic capital market institute expand as one of the source acceptance of fund of society. This research aims to know the role of the Islamic capital market institute in improving the investment climate in the Indonesian Islamic finance industry. This Descriptive qualitative research was written pursuant to study literacy from various books and research journals related to Islamic economics and investment. Of inferential elite result that the Islamic capital market institute has a role in improving the investment climate at Indonesian Islamic finance in the form of amenity and choice alternative of the investment yield the rate of return mount. Observation of activity of institute financial technology by Otoritas Jasa Keuangan and BAPEPAM needed in observing the Islamic financial institution operational to guarantee the society fund security story; level inculcated at investment Islamic capital market institute products.